2020
DOI: 10.1002/jppr.1626
|View full text |Cite|
|
Sign up to set email alerts
|

Deprescribing tools: a review of the types of tools available to aid deprescribing in clinical practice

Abstract: The importance of deprescribing, which is the process of withdrawing an inappropriate medication, supervised by a healthcare professional with the goal of managing polypharmacy and improving outcomes, is increasingly recognised as part of good clinical care. With this, a number of tools have been developed with the purpose of aiding health professionals to deprescribe in regular practice. The types of tools vary significantly in their form and include tools to aid in the overall process of deprescribing (such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 56 publications
1
73
0
1
Order By: Relevance
“…86 Given the magnitude of overprescribing in older adults, deprescribing initiatives have been developed at an international level (IGRIMUP) 45 and national level in several countries, including Canada, the USA, and Australia, as a means to reduce excessive doses or to discontinue inappropriate drug therapy. A narrative review conducted by Reeve 87 categorises the available types of deprescribing tools, including those that provide general deprescribing guidance, those that are drugspecific, tools for identi fying potentially inappropriate medications (table), and those that are designed to engage patient participation. Tools developed to identify inappropriate medications can directly inform deprescribing and the deprescribing processes and often use inappropriate medication tools as one of their steps.…”
Section: The Deprescribing Process: Tools and Protocolsmentioning
confidence: 99%
“…86 Given the magnitude of overprescribing in older adults, deprescribing initiatives have been developed at an international level (IGRIMUP) 45 and national level in several countries, including Canada, the USA, and Australia, as a means to reduce excessive doses or to discontinue inappropriate drug therapy. A narrative review conducted by Reeve 87 categorises the available types of deprescribing tools, including those that provide general deprescribing guidance, those that are drugspecific, tools for identi fying potentially inappropriate medications (table), and those that are designed to engage patient participation. Tools developed to identify inappropriate medications can directly inform deprescribing and the deprescribing processes and often use inappropriate medication tools as one of their steps.…”
Section: The Deprescribing Process: Tools and Protocolsmentioning
confidence: 99%
“…A recent study conducted in Canada suggested that pharmacist-led deprescribing focused medication review minimised unnecessary and potentially harmful medications (30). There have been several tools to support HCPs to assuredly deprescribe harmful or unwanted medications (31). However, it is unknown as to which tools are more important to effectively deprescribing and improving patient outcomes particular to the Ethiopian context.…”
Section: Discussionmentioning
confidence: 99%
“…We contacted GPs in two German regions (Marburg and Hannover) using established relationships, either through teaching assignments or through primary care research networks. Study staff helped participating GPs to install the withdrawal of an inappropriate medication, supervised by a health care professional with the goal of managing polypharmacy and improving outcomes [3]. Yet physicians find it difficult to deprescribe as decisions need to be based on complex interacting factors, and medical evidence is often uncertain [4].…”
Section: Training and Recruitmentmentioning
confidence: 99%